How aware are swingers about their swing sex partners’ risk behaviours, and sexually transmitted infection status? - Niekamp, Anne-Marie (BMC Infect Dis, 2021)
BACKGROUND: Swingers are members of a heterosexual couple who, as a couple, have sex with others. They constitute a hidden subpopulation that is at risk for sexually transmitted infections (STIs). This study aimed to determine swingers’ level of awareness about the STI risk (indicators: bisexual behaviour, number of sex partners, and STI status) of their swing sex partners (i.e. alters). METHODS: In this cross-sectional study, data were collected from a convenience sample of swingers who visited our STI clinic. The sample consisted of 70 participants (i.e. egos) and their 299 swing sex partners (i.e. alters) who had undergone an STI test at our clinic. We compared network data (i.e. information that egos provided about alters) and data stored in the electronic patient record (EPR) in our clinic (i.e. information provided by alters themselves). We assessed the agreement (correct estimation, overestimation and underestimation) between the network data and EPR data using chi-squared tests. RESULTS: Egos underestimated the bisexual behaviours of 37% of their male alters and overestimated the number of sex partners of 54 and 68% of their male and female alters, respectively. Egos correctly estimated the STI statuses of only 22% of the alters who had an STI during the past six months. CONCLUSIONS: The participating swingers underestimated the bisexual behaviours of their male swing sex partners, overestimated their number of sex partners, and underestimated their positive STI status. Underestimating their alters’ STI statuses can cause swingers to underestimate their own STI risk and fail to implement preventive measures. The latter finding has implications for STI prevention. Therefore, more attention should be paid to swingers in general and the promotion of actual partner notification and STI testing among swingers in specific. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12879-021-05813-5.